Synergistic effect of Ni doping and oxygen vacancies on the visible light photocatalytic properties of Ag2O nanoparticles - De A.K.; Sinha I. (My University, 2025)
Chemisorbed oxygens on photocatalysts can be photo-excited and favorably generate reactive oxygen species like superoxide radicals. In the present research, we prepare oxygen vacancy (OV) mediated and Ni-doped Ag2O nanoparticles by similar hydrothermal protocols. Doping Ag2O by the higher oxidation state Ni enhanced the chemisorbed oxygen on the surfaces of the prepared nanoparticles but reduced the OV proportion. The inclusion of OVs widened the bandgap of Ag2O nanoparticles, which was also validated by density functional theory (DFT) calculations. DFT formation energy calculations indicated that the dopant Ni atom could be substituting an Ag site in the Ag2O lattice. X-ray diffraction (XRD) analysis showed that doping caused Ag2O lattice contraction possibly due to the smaller Ni substituting the larger Ag atom. X-ray photoelectron spectroscopy (XPS) analysis showed that OV-mediated Ag2O nanoparticles have a negative conduction band position and Ni-doping slightly narrowed the bandgap along with a more positive valence band position. DFT calculations also showed shifting of the density of states (DOS) due to Ni doping in OV Ag2O. Both OV mediated and Ni-doped Ag2O nanoparticles photocatalyzed ciprofloxacin (CIP) degradation under visible light irradiation. Increased chemisorbed oxygen due to Ni-doping enhances the CIP degradation rate. © 2022 Elsevier Ltd